PERAN SERTIFIKASI UNTUK MENINGKATKAN MOTIVASI DAN KEDISIPLINAN GURU DALAM MELAKSANAKAN PEMBELAJARAN - Adhar Adhar (Universitas Islam Negeri Ar-Raniry, 2013)
This paper examines the relevance of the discipline teacher certification in motivating teachers to implement the learning performance. The learning process has not been able to produce an excellent student as the results of the discipline teachers during the conducting the teaching-learning. The important factor to motivate the teachers is by getting a good through the certification program. Through teacher certification is expected to improve discipline and motivate teachers to have a good lesson plan and improve the quality of teaching-learning at schools. Besides, through certification program, the teachers are better prepared to implement appropriate disciplinary learning lesson plan that has been established at the beginning of the school year. While other important activities, that the teachers are hoped to be able to carry out the learning evaluation at formal education units consistently through the assessment of daily tests, assignments, mid-term and semester examination. The evaluation activity must also be conducted regularly and sustainably in order to improve the quality of teaching in schools. These totally have been conducted well by the certified teacher to manage the class profesional ly in each school.